JORGE PÉREZ JARAMILLO - Medellín. Urbanismo y sociedad - Garrido, Ginés (ZARCH, 2023)
Jorge Pérez JaramilloMedellín. Urbanismo y sociedadMadrid: Turner, 2019. 256 pp. Tapa blanda. Idioma: español. 22,00 €ISBN: 9-788417-866099